Working Memory Screening in Latin American Children: Psychometric Properties of a Spanish Version of the Working Memory Rating Scale. Issue 3 (2nd July 2020) - Vernucci, Santiago; Galli, Juan Ignacio; Andrés, María Laura; Zamora, Eliana Vanesa; Richards, María Marta; Canet-Juric, Lorena; Burin, Débora Inés
ABSTRACT: The present study analyzes the psychometric properties of a Spanish-adapted version of the Working Memory Rating Scale (WMRS). This instrument allows teachers to perform a screening of children with possible working memory (WM) difficulties, putting them at risk of academic underachievement. A sample of children age 8.5 to 12.33 years old was evaluated with the WMRS, objective WM measures, and academic skills measures. Results indicated that WMRS scores were negatively correlated with objective WM and academic measures. Confirmatory factor analysis showed that a one-factor model had an adequate fit, and that the complete version of the scale was comparatively better than a short 5-item version. The WMRS was effective in differentiating children with low and average WM. These results indicate that the Spanish version of the WMRS presented adequate psychometric properties, and may be useful for teachers in Latin America for screening children with WM difficulties.